Optimizing coagulant choice for treatment technology of surface water for human consumption - Wolska, Małgorzata; Mołczan, Marek; Urbańska-Kozłowska, Halina; Solipiwko-Pieścik, Anna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The results of optimizing the coagulant choice for surface water treatment for human consumption have been presented. This optimization included not only elimination of organic matter from water with low contamination levels but also determining the cost of the process. Ten coagulants differing in aluminum content and in preliminary hydrolysis have been examined. The costs were calculated for four most effective coagulants.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 131-141
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma